Common Law and Enlightenment in England, 1689-1750 - Rudolph, Julia, 1962- (Studies in early modern cultural, political and social history., 2013)
The book demonstrates how the 'common law mind' was able to meet the various challenges posed by Enlightenment rationalism and civic and commercial discourse, revealing that the common law played a much wider role beyond the legal world in shaping Enlightenment concepts.